One-pot expeditious synthesis of glycosylated esters through activation of carboxylic acids using trichloroacetonitrile. (November 2022) - Yadav, Mangal S.; Jaiswal, Manoj K.; Kumar, Sunil; Singh, Sumit K.; Ansari, Faisal J.; Tiwari, Vinod K.
Abstract: Acetimidates, a valuable intermediate has been well explored as versatile synthon in a number of organic transformations particularly as suitable donors in glycosylation reactions. Herein, we explored acetimidates to furnish high-to-excellent yield of diverse glycosylated esters under one-pot mild reaction condition. The commercially available trichloroacetonitrile is implemented for the activation of carboxylic acid via in situ generation of trichloroacetimidate, which was subsequently attacked by sugar alcohols to deliver high-to-excellent yields of desired glycosylated esters. The devised method has some notable features such as metal-free condition, one-pot mild reaction condition, easy-handling, high-to-excellent yields, and broad substrate scope. Graphical abstract: Image 1 Highlights: Acetimidate is well-known valuable intermediate that greatly utilized in organic synthesis notably as donors in glycosylation reaction. For the first time, we explored acetimidates to furnish high-to-excellent yield of diverse glycosylated esters under one-pot mild reaction condition. The trichloroacetonitrile is implemented for the activation of carboxylic acid via in situ generation of trichloroacetimidate, which was then reacts with sugar alcohols to deliver the desired glycosylated esters. The metal-free and one-pot mild reaction condition, easy-handling, high-to-excellent yields, and broad substrate scope are the notable features of devised method.